PENGARUH PENGGUNAAN MEDIA GAMBAR DALAM PEMBELAJARAN SEJARAH - Alief Lukman Hakim; Yunita Anggraini; Risha Fitriani; Arghob Khofya Haqiqi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2019)
Social science is one of the subjects given at the level of primary and secondary education, and one of the studies of social science taught is history, but in reality students actually do not like the subject of social science because it is synonymous with memorization so it feels boring and lazy to learn it, it is recorded in the history of learning that has a lot of material discussed about the past. To create a quality and enjoyable learning process, the teacher must be innovative in learning, one of which is learning using picture media. The method of data collection used is through library study techniques or library studies obtained through various sources from books and journals. This scientific paper was made to find out how the influence of the use of picture media in historical learning on student learning outcomes.